Uterine torsion in Simmental crossbreed cow - Rahayu, Sri (Universitas Airlangga, 2022)
This case report describes the treatment of uterine torsion in Simmental crossbreed cattle. The dam was five years old, twice parity, in nine months and ten days pregnancy. Based on the anamnesis, it is known that the cows show signs of restlessness, straining, more robust by the time. However, there was no visible edema in the vulva, no ruptured membranes, no legs and head of the fetus coming out of the dam's vulva. Tretment was carried out by traditional rolling until the maximum uterine lumen opening was obtained. The position of the fetus is head flexion posture, so to remove it vaginally, the head is repositioned first and then forced to pull it out until the fetus comes out. Post-treatment, the dam's condition was still weak, unable to stand up, did not want to eat, and only drank a little. The drugs given were analgesics-antipyretics (repeated in the afternoon), long-acting antibiotics, vitamin B1, and vitamins and minerals mixed. After a few hours, the dam was up and walking around, feeding and drinking, and the placenta completely separated. The fetus's condition was alive, female sex, weak condition, the condition improves after being given milk from the dam. It can be concluded that the case of uterine torsion in Simmental crossbreed cows has been successfully treated 24 hours after the signs of birth using the traditional rolling technique, and the fetus can be expelled vaginally. The condition of the dam and fetus after the treatment of uterine were torsion gradually became healthy.